República e educação : dos princípios da Escola Nova ao Manifesto dos Pioneiros da Educação - Alves, Luís Alberto Marques (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The fi rst decades of the twentieth century brought a profound refl ection about the new direction of the school, the contents of education, the new role of teachers and the best methodologies to reach the recipients. In this article we seek to systematize the essential ideas that the New School Movement (Europe and USA, mainly) and the Manifesto of the Pioneers of Education (Brazil) brought to the major educational changes of the fi rst half of the twentieth century.